2019
DOI: 10.1002/ange.201905803
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Carbon/g‐C3N4 Composite Negative Electrode for a Long‐Life Sodium‐Ion Battery

Abstract: 2D graphitic carbon nitride (g-C 3 N 4 )nanosheets are ap romising negative electrode candidate for sodium-ion batteries (NIBs) owing to its easy scalability,low cost, chemical stability,and potentially high rate capability.However,intrinsic g-C 3 N 4 exhibits poor electronic conductivity,l ow reversible Na-storage capacity,a nd insufficient cyclability.D FT calculations suggest that this could be due to al arge Na + ion diffusion barrier in the innate g-C 3 N 4 nanosheet. Afacile onepot heating of am ixture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…DFT studies of pure carbon nitrides for large-sized metal ion batteries have also been reported. For instance, Weng et al showed that pure C 3 N 4 nanosheet displays high adsorption energy for Na-atom, but it shows an exceedingly high diffusion barrier, which makes it fail as a SIBs anode [53]. Moreover, through DFT we showed that thanks to the high pyridinic-N of 1 3…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…DFT studies of pure carbon nitrides for large-sized metal ion batteries have also been reported. For instance, Weng et al showed that pure C 3 N 4 nanosheet displays high adsorption energy for Na-atom, but it shows an exceedingly high diffusion barrier, which makes it fail as a SIBs anode [53]. Moreover, through DFT we showed that thanks to the high pyridinic-N of 1 3…”
mentioning
confidence: 74%
“…Weng et al reported the synthesis of a C/g-C 3 N 4 composite via a simple one-pot synthesis approach, and the composite delivered a capacity of 254 mAh g −1 at 0.1 A g −1 and 160 mAh g −1 at 0.4 A g −1 (see Fig. 20g) [53]. Recently, Chen et al showed that coating the surface of copper metal current collector with a thin film of 2D-C 3 N 4 can improve Na storage by inhibiting unwanted surface interaction with the liquid electrolyte.…”
Section: Sodium and Potassium-ion Batteries (Sibs And Pibs)mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2e, for bulk g‐C 3 N 4 and CoPc, the binding energy of C 1s at 284.6, 286.2, and 288.3 eV can be corresponding to the typical graphitic sp 2 CC, CO, and CNC, respectively. [ 25,34 ] The characteristic peak of carboxyl (OCOH) for C 1s at 288.7 eV emerges in CoPc/g‐C 3 N 4 compared with other two samples, which can be attributed to the mechanochemical interaction between CoPc and g‐C 3 N 4 with adsorbed oxygen and moisture during BM process. [ 35 ] Furthermore, the XPS survey spectra for the samples of CoPc‐BM and g‐C 3 N 4 ‐BM nanosheets were also performed and further confirmed the significantly introduced oxygen species after BM process, as shown in Figure S6 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] More importantly, the g‐C 3 N 4 with abundant pyridinic N sites can create the microelectric field effects on CoPc molecule and lead to a negatively charged surface of catalyst, [ 24 ] and have an ability of Na + adsorption and storage. [ 25 ] In this way, it is expected that the catalyst can equip with an ability for Na + adsorption in seawater, thus can lead to the suppressed HER and accelerate the CO 2 RR process. Therefore, it can be imagined that the selectivity and activity of CO 2 RR on CoPc molecular catalyst in seawater electrolyte can be modulated and improved through coupling g‐C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%